(untitled) (Orinoquia, 2016)
This study was aimed to correlate the immunoglobulin G (IgG) concentration with protein, minerals and color in 69 bovine colostrums from Bos taurus x Bos indicus crosses from a dual-purpose production system farm on Colombia in the piedemonte llanero during the first three days postpartum. IgG concentration in colostrum had a negative correlation with days postpartum whereas a positive correlation was found with protein, lactose and solid content in whole colostrum. The correlation between whole colostrum color and IgG concentration was positive for the b* value (r=0.182, p=0.024), located it in the range of blues and yellows. Mean IgG concentration for day one was 51,601 mg/ml, 23,319 mg/ml for day two and 36,534 mg/ml for day three. IgG concentrations were significantly higher on day 1 postpartum and inversely correlated with days postpartum (p<0.05). The number of calvings was not associated with IgG concentration (p>0.05). The bovine population evaluated produced good quality colostrum which can be used for transfer of passive immunity by using colostrum banks. Keywords: Immunoglobulin; ELISA; parturition; colour (AIMS; FAO)